Level Of Passing Skills In Soccer Learning - Rohmatullah Rohmatullah; Rina Marlina; Ruslan Abdul Gani (IKIP Budi Utomo Malang, 2020)
This study aims to learn the skills passed by learning ball class X students in Jasinga 1 High School. Using quantitative research with survey methods. The sampling technique used was purposive sampling with a total sample of 30 male students. The instrument used was the graduation skills test used by Jaelani (2014). Data analysis techniques using quantitative descriptive analysis techniques as outlined in the form of percentages. The results of research on skills that pass of soccer learning in class X of SMAN 1 Jasinga are in the category of